Distributional patterns of subchondral bone density and histopathological features of the first tarsometatarsal joint in hallux valgus feet - Yasunari Ikuta; Tomoyuki Nakasa; Junichi Sumii; Akinori Nekomoto; Nobuo Adachi (BMC Musculoskeletal Disorders, 2022)
Abstract Background Hypermobility of the first tarsometatarsal (TMT) joint is frequently identified in patients with hallux valgus (HV); however, its association with the development of osteoarthritis in the first TMT joint in such patients remains unknown. The purpose of this study was to clarify the distribution of subchondral bone density of the first TMT joint via computed tomography (CT) using Hounsfield units (HU). Methods Patients were divided into three groups: the osteotomy (20 feet; 20 women, mean age: 61.8 years), arthrodesis (23 feet; two men, 21 women, 71.2 years), and control group (patients without HV deformity who had undergone CT scans of the foot; 13 feet; seven men, six women, 29.7 years). The HU ratios were calculated, which were defined as the HU value of each subdivision of the subarticular spongiosa of the first TMT joint [dorsomedial (DM), dorsolateral (DL), plantomedial (PM), and plantolateral (PL)] divided by the HU values of the entire joint surface. The ratios for the osteotomy, arthrodesis, and control groups were compared. The degradation of the articular cartilage in the first TMT joint was histologically graded in the arthrodesis group. Tukey–Kramer multiple comparison analysis was conducted to compare the HU ratios among the three groups, and the histological grade in each subdivision. Results The arthrodesis group demonstrated high HU ratios in the DM area of the medial cuneiform, and significantly lower HU ratios in the PL area of the first metatarsal. Lower HU ratios in the DL area were observed in both the osteotomy and the arthrodesis group when compared to that in the medial cuneiform of the control group. The histological evaluation indicated nearly normal articular cartilage for all subdivided areas in both the medial cuneiform and the first metatarsal in patients with severe HV. Conclusions Although high subchondral bone density was identified in the DM area of the medial cuneiform in severe HV, only mild degradation was histologically observed in the articular cartilage of the first TMT joint. Our findings suggest that the indications for arthrodesis of the first TMT should be reconsidered based on the severity of the degenerative changes in the first TMT joint.